HLA Class II Profile: A Weak Determinant of Factor VIII Inhibitor Development in Severe Haemophilia A - Hay, C R M; Oilier, W; Pepper, L; Cumming, A; Keeney, S; Goodeve, A C; Colvin, B T; Hill, F G H; Preston, F E; Peake, I R; UKHCDO Inhibitor Working Party (Thrombosis and Haemostasis, 1997)
The risk of developing factor VIII inhibitor antibodies in haemophilia A may relate both to factor VIII genotype and genes within the HLA complex known to influence immune response. We investigated a cohort of 176 patients with severe haemophilia A and with either high-level inhibitors (>10BU/ml) or with no history of an inhibitor, stratified according to the presence or absence of the factor VIII gene intron 22 inversion.HLA DRB1, DQA1 and DQB1 polymorphisms were determined by PCR. HLA frequencies from 137 United Kingdom controls were used for comparison. HLA phenotype frequency differences, expressed as odds ratios with 95% confidence intervals were as follows: HLA- DRB*1501, DQB 1*0602 and DQA1*0102 were all increased in frequency in patients with inhibitors, only DQA1*0102 reaching statistical significance (OR 2.7,1.2-5.9). These alleles form part of an established HLA haplotype. The frequencies of HLA-DRB 1*1501, DQB1*0602 and DQA1*0102 were particularly raised in patients with inhibitors and a factor VIII gene intron 22 inversion, although again only DQA1*0102 achieved significance (OR 3.1, 1.0-10.1). The frequency of DRB 1*01, DQB 1 *0501, DQA 1*0101 were also increased in inhibitor patients lacking the intron 22 inversion although this failed to achieve statistical significance. This data suggests that HLA class II profile constitutes a weak risk factor for developing inhibitor antibodies to factor VIII. This may be more pronounced in patients with an intron 22 inversion.